Lerneca inalata beripocone subsp. nov. (Orthoptera: Phalangopsidae; Luzarinae): a new taxon for the northern Pantanal of Brazil - Lima, Raysa Martins; Martins, Luciano De Pinho; Pereira, Marcelo Ribeiro; Ganchev, Todor D.; Jahn, Olaf; Lhano, Marcos Gonçalves; Marques, Marinêz Isaac; Schuchmann, Karl-L (Zootaxa, 2016)
The first record of the Orthoptera species Lerneca inalata for Brazil is presented here. The taxon is represented by a new subspecies Lerneca inalata beripocone subsp. nov. (Phalangopsidae, Luzarinae), collected in the Pantanal of Poconé, Mato Grosso, Brazil. This work includes morphological and morphometric data as well as descriptions of female genitalia and calling song. The new subspecies has as diagnostic features the male genitalia with six ventral spines on the B sclerite, the first spine having a subtle bifurcation; the mid-region of the strongly sclerotized pseudepiphallus; inclination of C sclerite with slightly concave curvature; tegmina-length ratio and the speculum (syn. mirror) width approximately three times the length of the apical area. The description of the female genitalia and the calling song is presented for the first time for the species Lerneca inalata. A distribution map covers the local occurrence of its subspecies.